Andrographolide Activates Keap1/Nrf2/ARE/HO-1 Pathway in HT22 Cells and Suppresses Microglial Activation by Aβ42 through Nrf2-Related Inflammatory Response - Ji Yeon Seo; Euisun Pyo; Jin-Pyo An; Jinwoong Kim; Sang Hyun Sung; Won Keun Oh (Mediators of Inflammation)
Therapeutic approach of Alzheimer’s disease (AD) has been gradually diversified. We examined the therapeutic and preventive potential of andrographolide, which is a lactone diterpenoid from Andrographis paniculata, and focused on the Kelch-like ECH-associated protein 1 (Keap1)/nuclear factor (erythroid-derived 2)-like 2 (Nrf2)-mediated heme oxygenase (HO)-1-inducing effects and the inhibitory activity of amyloid beta (Aβ)42-induced microglial activation related to Nrf2 and nuclear factor κB (NF-κB)-mediated inflammatory responses. Andrographolide induced the expression and translocation of Nrf2 from the cytoplasm to the nucleus, thereby activating antioxidant response element (ARE) gene transcription and HO-1 expression in murine hippocampal HT22 cells. Andrographolide eliminated intracellular Aβ42 in BV-2 cells and decreased the production of interleukin (IL)-6, IL-1β, prostaglandin (PG)E2, and nitric oxide (NO) because of artificial phagocytic Aβ42. It decreased pNF-κB accumulation in the nucleus and the expression of inducible nitric oxide synthase (i-NOS) and cyclooxygenase II (COX-II) in the microglial BV-2 cell line. In summary, andrographolide activates Nrf2-mediated HO-1 expression and inhibits Aβ42-overexpressed microglial BV-2 cell activation. These results suggested that andrographolide might have the potential for further examination of the therapeutics of AD.